Upgrading in the Indian automobile sector: The role of lead firms - Saon Ray; Smita Miglani (Indian Council for Research on International Economic Relations (ICRIER), 2018)
This paper has made an attempt to identify the role of lead firms in mapping the activities related to upgrading. Upgrading refers to the process through which firms may move up the value chain. The literature identifies different types of upgrading such as product, process, functional and inter-chain upgrading which form the essential dynamics of the growth of a manufacturing industry. The Indian automobile industry is one of the successful cases in this regard. Using a case analysis approach, this paper looks at upgrading efforts made by seven major OEMs, including the use of advanced modular platforms, new materials and platform sharing among firms. The role of policy in facilitating the emergence and growth of lead firms has also been assessed.
Keywords: L2; F23; L62; O32; 330; Global value chains; automobile industry; organization of production; R&D